PERSEPSI SISWA TERHADAP KETERAMPILAN BERKOMUNIKASI GURU DALAM PROSES PEMBELAJARAN DI SMK KARTIKA 1-2 PADANG - SUCI HERAWATI (Jurnal Bahana Manajemen Pendidikan, 2016)
This article aims to obtain information about the perception of student toward teacher comunication skills in the study . This is a descriptive research with a population 94 people. The research sample is determined look at table Krejcie 76 people. The research instrument was questionnaire in the form of Likert Scale, which has proven its validity and reliability. Research data processing performed by using the average formula (mean). In general, the result of the research is the perception of student toward teacher comunications skills in the study is good with an average score 3,9.